Evaluation of aerodynamic characteristics of a ship with flettner rotors by wind tunnel tests and RANS-based CFD. (15th June 2022) - Kume, Kenichi; Hamada, Tatsuya; Kobayashi, Hiroshi; Yamanaka, Shota
Abstract: One wind propulsion system is the Flettner rotor, which utilizes the aerodynamic force generated by the Magnus effect as thrust by rotating a cylinder placed in a flow. The contribution of this type of system to the improvement of fuel efficiency when installed on board a ship can be quantified by Energy Efficiency Design Index (EEDI) specified in the MARPOL Convention. However, a reasonable estimation of the thrust generated by the Flettner rotors is required to properly account for the effects of the rotors in the EEDI. Therefore, in this study, the use of RANS-Based CFD to estimate the aerodynamic forces on a ship equipped with Flettner rotors is considered, and the results of CFD calculations and wind tunnel tests are compared in order to evaluate the accuracy of the CFD analysis. The results show that CFD calculations of the aerodynamic forces on a rotor-equipped ship with model-scale Reynolds numbers agree qualitatively and quantitatively with the results of wind tunnel tests using a scaled model, indicating that CFD can be used as a substitute for wind tunnel tests. Furthermore, the discussion in previous studies using the results of CFD carried out at Reynolds numbers corresponding to the full scale indicates that CFD is capable of predicting the performance of aerodynamic forces acting on a full-scale rotor if the L PP -based Reynolds number R e is more than 1.0 × 10 6 . Highlights: A ship with Flettner-rotors are evaluated by wind tunnel tests and RANS-Based CFD. The relationship between aerodynamic characteristics and Velocity Ratio is clarified. Aerodynamic characteristics comparable to those of tests can be obtained by CFD. Even at relatively low Reynolds numbers, evaluation of ship performance can be made.